Denser Retinal Microvascular Network Is Inversely Associated With Behavioral Outcomes and Sustained Attention in Children - Provost, Eline B.; Nawrot, Tim S.; Int Panis, Luc; Standaert, Arnout; Saenen, Nelly D.; De Boever, Patrick (Frontiers in Neurology, 2021)
Changes in geometry of the retinal microvascular network, including vessel width, vessel density and tortuosity, have been associated with neurological disorders in adults. We investigated metrics of the retinal microvasculature in association with behavior and cognition in 8- to 12-year-old children. Digital fundus images of 190 children (48.2% girls, mean age 9.9 years) were used to calculate retinal vessel diameters, fractal dimension, lacunarity, and tortuosity. Parents filled out a Strengths and Difficulties Questionnaire (SDQ) for behavioral screening. Cognitive performance testing included a computerized version of the Stroop test (selective attention), the Continuous Performance (sustained attention), the Digit-Symbol (visual scanning and information-processing speed) and the Pattern Comparison (visuospatial analytic ability) tests from the Neurobehavioral Evaluation System (NES3) battery. Retinal vessel geometry was significantly associated with the SDQ problem score, which increased with 1.1 points (95% CI: 0.3 to 1.9 points) for each interquartile (IQR) increment in retinal fractal dimension, and decreased 1.4 points (95% CI: 0.4 to 2.4 points) or 0.99 points (95% CI: -0.13 to 2.1 points) for each IQR increment in retinal vascular lacunarity or tortuosity, respectively. Sensitivity analyses showed that results were driven by the hyperactivity/inattention and conduct problem scales of the SDQ. Correspondingly, mean latency on the Continuous Performance test increased by 11 msec (95% CI: 4.4 to 17.6 msec) with an IQR increase in fractal dimension. The results indicate that a denser retinal microvascular network, exemplified by a higher fractal dimension, and lower lacunarity are inversely associated with behavior and sustained attention in primary school children.